A cell membrane-targeting AIE photosensitizer as a necroptosis inducer for boosting cancer theranostics. Issue 20 (3rd May 2022) - Niu, Niu; Yu, Ying; Zhang, Zhijun; Kang, Miaomiao; Wang, Lei; Zhao, Zheng; Wang, Dong; Tang, Ben Zhong
Abstract : A membrane-targeting photosensitizer TBMPEI with AIE properties was synthesized via a new acceptor, and it was utilized as a necroptosis inducer during imaging-guided photodynamic therapy. Abstract : The exploration of cellular organelle-specific anchoring photosensitizers with both prominent fluorescence imaging behavior and extraordinary reactive oxygen species (ROS) production capability is highly in demand but remains a severe challenge for effective cancer theranostics involving photodynamic therapy (PDT). In this contribution, we developed a cell membrane-targeting and NIR-emission photosensitizer having an aggregation-induced emission (AIE) tendency. The AIE photosensitizer, namely TBMPEI, is capable of lighting up and ablating cancer cells by means of a necroptosis procedure enabling cell membrane rupture and DNA degradation upon light irradiation, endowing TBMPEI with impressive performance for both in vitro and in vivo fluorescence imaging-guided PDT.